Mycobacterial safety of meat cuts from BCG-vaccinated African buffaloes (Syncerus caffer) experimentally infected with Mycobacterium bovis - Michel, Anita Luise (University of Pretoria, 2024)
Dissertation (MSc (Wildlife Health, Ecology and Management))--University of Pretoria, 2024.